Legal Review Of The Framework "Without Consent" In Permendikbudristek Number 30 Of 2021 Related To Sexual Actions In Higher Education - Sylvani Sylvani; Winsherly Tan (ConCEPt - Conference on Community Engagement Project, 2023)
Sexual violence on college campuses has become an urgency, initiated by various parties, especially students. In response to this, the Minister of Education of Indonesia issued Regulation of the Minister of Education, Culture, Research, and Technology Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education . However, some people appear to have repudiation against the regulation, concerning the phrase "without consent", which seems to be allowing immoral actions and violating religious norms. This study is aiming to examine the meaning of the phrase "without consent" based on the regulatory context and analyze the legal protection provided. Normative legal research was used for this study. The results show that the phrase "without consent" in this case means when sexual violence occurs because of coercion and without the consent of the victim. And when it does happen, this regulation provides significant legal protection to the victims. The phrase â€œwithout consentâ€ provides clear parameters for cases to go through a legal process, as well as the establishment of a task force as the party responsible for handling sexual violence mechanisms from receiving reports, resolving cases, and providing recovery facilities for victims.